(untitled) (Research, Society and Development, 2021)
Candida albicans is the microorganism present in the oral mucosa responsible for about 95% of oral candidiasis. It is considered to be the main etiological factor in denture stomatitis, an inflammation process of the mucosa under the prosthesis. Antifungals are the most predominant treatment against c. albicans and demonstrate great efficacy despite many side effects, such as unpleasant taste, allergies and gastrointestinal reactions. Phytotherapy has been showing promise as an alternative therapy due to its advantages, mainly the antimicrobial effect and the reduction of adverse side-effects. Thus, the objective of this scoping review is to systematically explore the literature, to map and to summarize the available evidence regarding the use of natural products in the treatment of oral candidiasis. This protocol was developed in accordance with the recommendations of the Joanna Briggs Institute Manual and registered with Open Science Framework. The search for the articles will be carried out in three stages, using the PubMed, Scopus, Web of Science, Embase, Cochrane Library and LILACS databases, as well as additional sources of gray literature and reference lists of included studies. The terms “phytotherapy”, “biological products”, “oral candidiasis", “denture stomatitis", "candida albicans", and their related words will be used in this strategy. The data will be extracted into a form and presented as tables and/or images and as a narrative. This protocol will assist in the development of the scoping review to identify gaps and synthesize knowledge for the conduct of future primary studies.